The Influence of Adaptive Work Culture on the Performance of Smart Energy Solar Cell Utilization in the Tofu Industry - Nur, Meilani; Rahmawati, Dayyinah Ayunda (Institute Of Advanced Knowledge and Science, 2025)
This research explores the influence of adaptive work culture on the performance of smart energy solar cell utilization in the tofu industry. As the tofu industry increasingly adopts renewable energy technologies like solar power, understanding the role of employees' adaptability to these changes becomes crucial. The study utilizes a quantitative approach with a sample size of 30 employees involved in the implementation and operation of solar energy systems in tofu production. Data were analyzed using SmartPLS 24 software, applying several analytical methods, including validity, reliability, multicollinearity, R-square, and hypothesis testing. The research finds a significant positive relationship between adaptive work culture and the effective performance of solar energy systems, with key factors such as work flexibility, openness to change, and learning ability contributing to higher operational efficiency and system optimization. The results indicate that fostering an adaptive work culture within the workforce leads to better management, maintenance, and utilization of solar energy technology, enhancing overall production outcomes. Based on these findings, the study concludes that businesses in the tofu industry, and similar small-scale industries, should prioritize cultivating an adaptive work culture to successfully integrate and optimize renewable energy technologies.